A baseline assessment of antimicrobial stewardship core element implementation in selected public hospitals in Malawi: findings from the 2023 National Program Audit - Chitatanga, Ronald; Yiwombe, Chikhulupiliro; Divala, Oscar; Msokera, Mwayi Prudence; Banda, Ellen; Chadwala, Hope; Gilmon, Manuel Wellington; Kaminyoghe, Wezi; Chibwe, Innocent; Milala, Harry; Kawerama, Alinafe; Nyoni, Kenneth; et al. (Frontiers in Public Health, 2025)
BackgroundAntimicrobial resistance (AMR) is a significant global health challenge, particularly in low- and middle-income countries (LMICs). In Malawi, frequent stockouts of essential medicines and the widespread dispensing of antibiotics without prescriptions have exacerbated the AMR burden, highlighting the urgent need for robust antimicrobial stewardship (AMS) interventions. This study presents the first documented baseline assessment of AMS core elements across six public healthcare facilities within Malawi’s AMR sentinel surveillance network. Understanding the baseline status of AMS implementation provides a critical reference point to guide future interventions, inform policy, and prioritize resources in the national response to AMR.Materials and methodsThis descriptive analysis used data from a national AMS program audit conducted from July 10–14, 2023, in six public hospitals: Malamulo Adventist Hospital, Mzimba South District Hospital, Kamuzu Central Hospital, Queen Elizabeth Central Hospital, Zomba Central Hospital, and Mzuzu Central Hospital. The World Health Organization (WHO) Healthcare Facility AMS Assessment Tool was used to evaluate implementation across key AMS domains, including leadership, accountability, stewardship actions, education, monitoring, surveillance, and reporting. A total of 30 AMS committee members participated using a consensus-based approach.ResultsOf the six hospitals assessed, only one (Kamuzu Central Hospital) demonstrated strong implementation of AMS core elements, achieving a score of 79%. The remaining facilities reported moderate to low performance, with Mzimba District Hospital scoring the lowest (24%). Leadership commitment was inconsistent; only one (16.7%) hospital had fully integrated AMS into its annual plans, and resource allocation was limited. AMS ward rounds and antibiotic prescription audits were either absent or only partially implemented across most facilities. Education and training initiatives were fragmented, with only one (16.7%) hospital partially integrating AMS into staff induction.ConclusionThis situational analysis reveals critical gaps in AMS implementation across Malawi’s national AMR surveillance hospitals. Limited leadership commitment, infrequent AMS ward rounds, and inconsistent education for healthcare workers were major barriers. Targeted interventions are needed to strengthen leadership, establish feasible facility-level AMS actions, and build sustainable capacity among healthcare workers.